Stigmasterol and Stigmasterone from Methanol Extract of Calophyllum soulattri Burm. F. Stem Bark - Surya Dewi Marliyana; Fajar Rakhman Wibowo; Desi Suci Handayani; Triana Kusumaningsih; Venty Suryanti; Maulidan Firdaus; Ema Nur Annisa (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2021)
Stigmasterol and Stigmasterone from Methanol Extract of Calophyllum soulattri Burm. F. Stem Bark. Calophyllum soulattri Burm. F. has been widely used for herbal medicine. Phytochemical investigation of C. soulattri contains a secondary metabolite of the steroid class. Steroid compounds have various biological activities, such as anti-inflammatory, antioxidant, antiproliferative, antibacterial, antimalarial, and anticancer. Two secondary metabolites steroids have been isolated and identified from the stem bark extract of C. soulattri. Isolation was carried out through the extraction (maceration), fractionation, and purification stages. Maceration is carried out using methanol as a solvent. Fractionation was carried out by vacuum liquid chromatography (VLC), and purification was by flash column chromatography. Identification of combined fractions and determination of pure isolates were used through thin-layer chromatography (TLC). The solvent used in the chromatography methods was a mixture of n-hexane and ethyl acetate. The structure isolates were identified by FTIR, 1H NMR, and 13C NMR and compared with literature data. Secondary metabolites steroids that have been isolated are identical compounds to stigmasterol and stigmasterone.